The development of low-fat beef burger using fat replacer ingredients - Sanchez Ma. Rosario Liamzon; De Leon, Sonia Y. (1994.)
The main objective of the study was to develop an acceptable low-fat beef burger formulation utilizing fat replacers such as Isolated Soy Protein and Carrageenan. In the first phase, the low-fat beef burger formulation using carrageenan had the highest general acceptability score at 3.10 compared to the fat-filled burger that was rated at 3.40 using a scale of 1-4 with 4 as being the most preferred. This was then reproduced at pilot scale, its proximate composition and microbial content was examined. Results from its proximate analysis showed that cooking loss was decreased from 39.4% to 29% and that a fat reduction from 19.12% to 1.70% was made possible without impairing flavor, however further improvement needs to be done on its textural properties. For the last phase, a consumer survey involving 100 persons showed that 45% of the consumers surveyed found the finished product to be comparable with commercially-sold burgers and that 84% were willing to buy the finished product if introduced in the market.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beef; Cookery (Beef)